Prehistory of Aadhaar: Body, Law, and Technology as Postcolonial Assemblage. Issue 4 (1st December 2018) - Abraham, Itty
Abstract: This article seeks to go beyond the binary of elite concerns over privacy versus subaltern desires for recognition to understand the huge Indian biometric project, Aadhaar. It offers a prehistory of Aadhaar, framed not in terms of rights and wrongs, important as they are, but as the most recent project in the shaping of modern social and political power through the technologically mediated intersection of the law and the body. Key moments of technopolitical reduction of the physical body—fingerprinting, DNA tests, brain scans, polygraphs, and truth serums—become turning points in a process that have joined personal identity with evidentiary truth to overcome centuries of judicial skepticism. Due to its combined technopolitical and biological foundations, the new national database commands a high degree of social and political confidence as reflected in the unplanned and unforeseen expansion of Aadhaar. In this emergent database society, intersections of law, body, and technoscience engender new human networks: temporary alliances among material forces, inanimate techniques, discourses, norms, and institutions, organized around the technologically mediated body. This article proposes in conclusion that, as a result of these developments, we are likely to see the generation of new and unverifiable conceptions of what we mean by and how we represent the ultimate human network, "society."